Investigation of synthesis peculiarities inherent to computer-generated rainbow holograms of 3D images - Girnyk, V.I.; Kostyukevich, S.A.; Shepeliavyi, P.E.; Kononov, A.V.; Borisov, I.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
This work deals with Computer-Generated Rainbow Holograms (CGRHs), which can restore the 3D images under white light. They are devoted to include in Diffractive Optically Variable Image Devices (DOVIDs) that are currently widely used for security needs. CGRHs prevent counterfeiting due to the complexity of recreation, on the one hand, and allow the simple identification at the first (visual) level of verification, on the other hand. To record it, the Electron Beam Lithography (EBL) is used. As recently proved, this method is a most promising for multi-level optical-digital security devices using chalcogenide glasses as resists.
The CGRH computation process is conventionally divided by two parts: synthesizing and recording. On the synthesis stage, firstly, the geometrical and optical constants of recording scheme are determined; secondly, the basic parameters accounting for discretization of Interferogram Data (ID) in hologram plane are defined and, finally, the calculation of the
ID - the array of Bipolar Intensity (BI) values - is carried out. This calculation is performed separately in each independent horizontal slice of object space and hologram plane. On the recording stage, suitable quantization parameters are chosen and transformation of ID into the multilevel rectangle data appropriate for EBL is accomplished.
The investigations on optimization of synthesis and recording of the multilevel CGRHs of 3D images integrated in Polygrams are presented here. So the rules for definition of the appropriate discretization parameters were finding out. Advantages of using non-linear quantization that implies condensing of quantization levels near the BI zero were explored. The random deviation of location and direction of elemental hybrid radiating area was applied. Practical applications of the method developed were made using chalcogenide semiconductors of various As-S-Se compositions.